Decennial Liability under UAE Law (Articles 880-883 of Law No. 5 of 1985) - SAMRAJ, ASHOK CHAKARAVARTHY (2018)
Decennial Liability is an exceptional liability in UAE, under Articles 880 to 883 of Law No. 5 of 1985. According to this provision of the Law, the Architect / Engineer (A/E) and the Contractor are jointly and severally liable to the Employer, for partial, or total collapse, or defects threatening the stability, or safety of the structure. Since decennial liability is a matter of public policy, it cannot be exempted or contracted out. Due to the paucity of literature and lack of published data with regard to the implementation and specific liability to A/E and the Contractor in various methods of procurements and executions models, there is prevalent misapprehension and presumptions among the construction professionals about application of certain provisions of the law. Decennial liability provisions in UAE Law appears to have drafted considering to projects procured through the traditional procurement route. However, in recent decades, new procurement methods and technologies have developed in the construction industry and it is likely that the current provisions of the Law have not addressed the specific liability implications and stakeholders of these new methods and technologies. This dissertation aims to examine the provisions of the decennial liability law of UAE to clarify and dispel prevalent misapprehensions and presumptions of construction professionals and analyze whether the provisions are applicable / sufficient enough for projects procured under new procurement methods and structures built using new technologies. In addition, this dissertation compares the provisions on decennial liability under UAE law with similar provisions in other GCC countries, Egypt and French law. This study will enlighten the constructional professionals about the decennial liability law in practice around the region and the research findings of this study may be used as guidance for contractual and legal liabilities they are subject to, for the latent defects.